Including reliability in the AASHTO-93 flexible pavement design method integrating pavement deterioration models - Rodríguez Moreno, Mario Alberto; Echaveguren Navarro, Tomás; Thenoux Zeballos, Guillermo (Revista de la Construcción. Journal of Construction, 2017)
The reliability used in the pavement design is assigned according to recommendations of design guides or according to the designer’s criteria; that is to say, there is no rational tool for their estimation. In addition, the chosen value is deterministic and does not consider the random nature of the process or the actual conditions of load, climate, material behavior and impact of the construction process that affect the performance of the structure when it is in service. This research proposes to link the design method and calibrated deterioration models to local conditions that consider the actual behavior of the materials, the variability of the construction process, the actual load stresses and the weather, when in operation. For this, a Monte Carlo simulation model is developed, using field data and statistical concepts that allow defining the variables of the model as random variables. Subsequently, with the variables found and using the reliability theory and the serviceability model, the design method and the models of deterioration are evaluated through a supply and demand analysis to obtain the reliability value that reduces the uncertainty of the performance of the structure when operating.